INFLUENCE OF ATTRIBUTES OF SELF-REGULATED LEARNING ON E-LEARNING IN SECONDARY SCHOOL STUDENTS - Vijayan, Vidhu; M, Harikrishnan; Kachroo, Arti Koul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Online learning, a solitary experience for the students? Are they studying in isolation?Is it satisfying?How can we design an approach that is more learner-centric?Students vary in their learning styles and characteristics.How can we make them more successful? If students are made aware of their learning style and characteristics,can't they learneffectively through a virtual platform?If students are aware of SRL(Self-regulation learning) skills,they will be able to plan their learning correctly,which will lead to an increase in their academic performance. The newness of online education has not allowed course content introduction effectively.Teachers need to guide the students to develop Self-regulation skills. Teachers must modify their lesson plan; a matching teaching style should be implemented after understanding the varied learning style.So this study addresses the influence of learner SRL skills on e-learning effectiveness among secondary school students.